In Vitro Antibacterial Effectiveness of Stingless Bee Propolis against Infected Breast Cancer Ulcer - Manginstar, Christian; Merung, Marselus; Albert, Albert (Universitas Sam Ratulangi, 2026)
Abstract: Breast cancer is the most common cancer in women and often presents with malignant ulcers prone to infection. These wounds are difficult to manage, especially during chemotherapy, due to polymicrobial colonization and rising antibiotic resistance. Stingless bee propolis, rich in bioactive flavonoids, has shown promising antibacterial properties. This study aimed to evaluate in vitro antibacterial effectiveness of stingless bee propolis against bacteria from breast cancer ulcers. This was an in vitro study conducted at the Poltekkes Kemenkes Manado Medical Laboratory (July 2024–January 2025). Methanol-extracted stingless bee propolis was tested against MRSA and P. aeruginosa using disc diffusion, MIC, and MBC methods. Antibacterial activity was evaluated through inhibition zones and bacterial growth in serial dilutions. The outcomes were analyzed based on inhibition zone diameters and bacterial growth in serial dilutions. The results showed that propolis extract demonstrated antibacterial activity against MRSA and P. aeruginosa, with inhibition zones observed in both disc diffusion and dilution methods. Strong inhibition was noted at concentrations ≥80%, while minimal or no effect occurred below 30%. MIC and MBC were estimated at around 20%. Statistical analysis confirmed a significant dose-response relationship (ANOVA, p 0.0003), with stronger correlation in MRSA (R=0.84; p<0.001) than P. aeruginosa (R=–0.09; p 0.046). The minimum effective concentration was estimated at 32% for MRSA and 37% for P. aeruginosa. In conclusion, stingless bee propolis demonstrated concentration-dependent antibacterial activity against both Gram-positive (MRSA) and Gram-negative (P. aeruginosa) bacteria in vitro, with increased activity observed at higher concentrations. Minimum effective concentrations were 32% for MRSA and 37% for P. aeruginosa, supporting its potential use in treating infected breast cancer ulcers. These findings highlight propolis as a potential natural alternative for infection control and wound healing. Keywords: breast cancer; ulcer; stingless bee; propolis; antibacterial effect